2022
DOI: 10.1111/tpj.15735
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of cis‐elements and identification of transcription factors putatively involved in the regulation of the OAS cluster genes SDI1 and SDI2

Abstract: SUMMARY Arabidopsis thaliana sulfur deficiency‐induced 1 and sulfur deficiency‐induced 2 (SDI1 and SDI2) are involved in partitioning sulfur among metabolite pools during sulfur deficiency, and their transcript levels strongly increase in this condition. However, little is currently known about the cis‐ and trans‐factors that regulate SDI expression. We aimed at identifying DNA sequence elements (cis‐elements) and transcription factors (TFs) involved in regulating expression of the SDI genes. We performed in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 129 publications
0
15
0
Order By: Relevance
“…Next, we checked the transcriptional response to high glucose of the selected genes known to respond to sulfur deficiency in a SLIM1-dependent manner, namely SULFUR DEFICIENCY-INDUCED 1 ( SDI1 ) and RESPONSE TO LOW SULFUR 1 ( LSU1 ) ( Wawrzynska and Sirko, 2016 ; Rakpenthai et al , 2022 ). Both genes belong to so-called ‘OAS cluster’ genes as their expression follows O -acetylserine (OAS; cysteine backbone) diurnal fluctuations, but they are also on the list of genes that are regulated by SLIM1 ( Maruyama-Nakashita et al , 2006 ; Hubberten et al , 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we checked the transcriptional response to high glucose of the selected genes known to respond to sulfur deficiency in a SLIM1-dependent manner, namely SULFUR DEFICIENCY-INDUCED 1 ( SDI1 ) and RESPONSE TO LOW SULFUR 1 ( LSU1 ) ( Wawrzynska and Sirko, 2016 ; Rakpenthai et al , 2022 ). Both genes belong to so-called ‘OAS cluster’ genes as their expression follows O -acetylserine (OAS; cysteine backbone) diurnal fluctuations, but they are also on the list of genes that are regulated by SLIM1 ( Maruyama-Nakashita et al , 2006 ; Hubberten et al , 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…As such, the co-expressed genes are presumably part of a complex regulatory network integrating diverse inputs, eventually regulating plant cell homeostasis. This is reflected by the fact that the promoters of OAS cluster genes analyzed so far contain diverse sets of cis -elements, and various TFs have been identified to affect their respective expression ( Rakpenthai et al , 2022 ).…”
Section: Functional Relationships Between the Genes Of The Oas Cluste...mentioning
confidence: 99%
“…Jasmonate application induces the expression of numerous genes involved in sulfur assimilation, methionine biosynthesis, SAM biosynthesis, and further sulfur-related processes ( Jost et al , 2005 ) and SDI1 ( Rakpenthai et al , 2022 ). Transcriptome analyses of plants under sulfur-deprived conditions revealed that genes of MeJa biosynthesis are induced within 24–48 h ( Hirai et al , 2003 ; Nikiforova et al , 2003 ; Jost et al , 2005 ).…”
Section: Oas Sulfur Metabolism and Their Connection With Hormonesmentioning
confidence: 99%
See 2 more Smart Citations